Balance abilities of junior ice hockey players - Ondra, L.; Svoboda, Z. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Postural control is required during various fast-paced and offensive ice hockey actions, and therefore seems to be an important component in ice hockey performance. METHODS: Data were collected from two ice hockey teams with differing performance levels. The higher-performance team consisted of 26 players (with ages of 16.3±0.9 y, heights of 178.26±6.71 cm, and weights of 74.3±9.6 kg). The lower-performance team consisted of 19 players (with ages of 16.2±1.8 y, heights of 176.11±9.81 cm, and weights of 68.7±13.9 kg). Each participant performed six unilateral stances under static conditions on a balance pad placed on a force platform and five bilateral stances under dynamic conditions using a wobble board placed on the force platform. RESULTS: The higher-level players performed better in the unilateral static stance task in both the anterior-posterior direction and the medial-lateral direction (with a P value of P<0.001), and total velocity (P=0.001). The higher-level players also performed better in both the anterior-posterior and medial-lateral directions, and total velocity (with P value of P<0.001), in the bilateral dynamic stance task and therefore performed significantly better than the lower-level players. CONCLUSIONS: Hockey players who possess a highly developed postural control strategy have a superior ability to compensate for unexpected postural disturbances and collisions, and thus possess a strong competitive advantage. Therefore, testing the balance abilities of hockey players under static and dynamic conditions may be useful for evaluating their competitive performance levels.